Efficacy and Safety of Trastuzumab Deruxtecan in Patients With HER2-Expressing Solid Tumors: Primary Results From the DESTINY-PanTumor02 Phase II Trial - Meric-Bernstam, Funda; Makker, Vicky; Oaknin, Ana; Oh, Do-Youn; Banerjee, Susana; González-Martín, Antonio; Jung, Kyung Hae; Ługowska, Iwona; Manso, Luis; Manzano, Aránzazu; Melichar, Bohuslav; Siena, Salvatore; et al. (Journal of clinical oncology, 2024)
PURPOSE: Trastuzumab deruxtecan (T-DXd) is a human epidermal growth factor 2 (HER2)-directed antibody-drug conjugate approved in HER2-expressing breast and gastric cancers and HER2-mutant non-small-cell lung cancer. Treatments are limited for other HER2-expressing solid tumors. METHODS: This open-label phase II study evaluated T-DXd (5.4 mg/kg once every 3 weeks) for HER2-expressing (immunohistochemistry [IHC] 3+/2+ by local or central testing) locally advanced or metastatic disease after ≥1 systemic treatment or without alternative treatments. The primary end point was investigator-assessed confirmed objective response rate (ORR). Secondary end points included safety, duration of response, progression-free survival (PFS), and overall survival (OS). RESULTS: At primary analysis, 267 patients received treatment across seven tumor cohorts: endometrial, cervical, ovarian, bladder, biliary tract, pancreatic, and other. The median follow-up was 12.75 months. In all patients, the ORR was 37.1% (n = 99; [95% CI, 31.3 to 43.2]), with responses in all cohorts; the median DOR was 11.3 months (95% CI, 9.6 to 17.8); the median PFS was 6.9 months (95% CI, 5.6 to 8.0); and the median OS was 13.4 months (95% CI, 11.9 to 15.5). In patients with central HER2 IHC 3+ expression (n = 75), the ORR was 61.3% (95% CI, 49.4 to 72.4), the median DOR was 22.1 months (95% CI, 9.6 to not reached), the median PFS was 11.9 months (95% CI, 8.2 to 13.0), and the median OS was 21.1 months (95% CI, 15.3 to 29.6). Grade ≥3 drug-related adverse events were observed in 40.8% of patients; 10.5% experienced adjudicated drug-related interstitial lung disease (ILD), with three deaths. CONCLUSION: Our study demonstrates durable clinical benefit, meaningful survival outcomes, and safety consistent with the known profile (including ILD) in pretreated patients with HER2-expressing tumors receiving T-DXd. Greatest benefit was observed for the IHC 3+ population. These data support the potential role of T-DXd as a tumor-agnostic therapy for patients with HER2-expressing solid tumors.
Keywords: Receptor, ErbB-2; Breast Neoplasms; trastuzumab; receptor erbB-2; nádory plic; Lung Diseases, Interstitial; intersticiální plicní nemoci; ženské pohlaví; nemalobuněčný karcinom plic; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Carcinoma, Non-Small-Cell Lung; Immunoconjugates; nádory prsu; Trastuzumab; imunokonjugáty; Female; Lung Neoplasms; lidé